Evaluation of WHO criteria to determine degree of dehydration in children with acute diarrhea - Suprawita Sari; Supriatmo Supriatmo; S L Margaretha; S Nafianti; B Hasibuan; A B Sinuhaji (Paediatrica Indonesiana, 2005)
Objective To evaluate the diagnostic accuracy and agreementbetween the 1980 and 1990 WHO criteria for determining the de-gree of dehydration in children with acute diarrhea.Methods This prospective study was conducted in two hospitalsfrom October 2002 to February 2003. Clinical signs of dehydrationall patients were recorded. The degree of dehydration based onthe 1980 and 1990 WHO criteria was determined and comparedwith fluid deficit measured by the difference of body weight on ad-mission and on discharge. Chi-square test and kappa value analy-ses were performed. Sensitivity, specificity, predictive values, andaccuracy of each WHO criteria were assessed. The prevalence ofdehydration was also determined.Results Sixty-five patients, comprising 40 boys and 25 girls, werestudied. There was a significant difference between the two WHOcriteria in differentiating between dehydration and non-dehydra-tion (P<0.05). Based on the 1980 WHO criteria the prevalence ofdehydration was 62.2%. Its sensitivity, specificity, and accuracy indiagnosing dehydration were 100.0%, 55.5%, and 86.2%, respec-tively. Based on the 1990 WHO criteria, the prevalence of dehy-dration was 60.0%. Its sensitivity, specificity, and accuracy in diag-nosing dehydration were 94.9%, 46.1%, and 75.4%, respectively.There was also a significant difference between both criteria indetermining severe dehydration (P<0.05). Based on the 1980 cri-teria, the prevalence of severe dehydration was 15.4%. Its sensi-tivity, specificity, and accuracy in diagnosing severe dehydrationwere 30.0%, 94.5%, and 84.6%, respectively. Based on the 1990criteria, these results were 40.0%, 94.5%, and 86.2%, respectively.The prevalence was 15.4%. Kappa value comparing the two WHOcriteria was 0.852 in diagnosing dehydration and 0.915 in diag-nosing severe dehydration. There was no significant differencebetween the two criteria in their sensitivity and specificity (P>0.05).Conclusion Both WHO criteria can be applied to determine de-hydration in patients with acute diarrhea, although we feel that the1990 criteria is simpler